Development of Patient Databases for Endocrinological Clinical and Pharmaceutical Trials: A Survey - Vezertzis, Konstantinos; Lambrou, George I.; Koutsouris, Dimitrios (Reviews on Recent Clinical Trials, 2020)
Background: According to European legislation, a clinical trial is a research involving patients, which also includes a research end-product. The main objective of the clinical trial is to prove that the research product, i.e. a proposed medication or treatment, is effective and safe for patients. The implementation, development, and operation of a patient database, which will function as a matrix of samples with the appropriate parameterization, may provide appropriate tools to generate samples for clinical trials. Aims: The aim of the present work is to review the literature with respect to the up-to-date progress on the development of databases for clinical trials and patient recruitment using free and open-source software in the field of endocrinology. Methods: An electronic literature search was conducted by the authors from 1984 to June 2019. Original articles and systematic reviews selected, and the titles and abstracts of papers screened to determine whether they met the eligibility criteria, and full texts of the selected articles were retrieved. Results: The present review has indicated that the electronic health records are related with both the patient recruitment and the decision support systems in the domain of endocrinology. The free and open-source software provides integrated solutions concerning electronic health records, patient recruitment, and the decision support systems. Conclusion: The patient recruitment relates closely to the electronic health record. There is maturity at the academic and research level, which may lead to good practices for the deployment of the electronic health record in selecting the right patients for clinical trials.
Keywords: Clinical trials